National surveillance of vectors and animal reservoirs - Rosický, B (Folia parasitologica, 1976)
In carrying out the national surveillance of vectors and animal reservoirs in Czechoslovakia the theory of the natural focus infections has been taken into account. In order to achieve a successful surveillance, besides studying the distribution of vectors and vertebrate hosts, the greatest emphasis has been put on the compilation of important data concerning their ecology, ethology and phenology. The author refers to some of the practical rsults of the national surveillance programme in Czechoslovakia.
Keywords: ekologie; Animals; Humans; Ecology; lidé; klíšťata; zvířata; hmyz - vektory; Arachnid Vectors; Insect Vectors; Czechoslovakia; arachnida jako vektory; Ticks; Disease Reservoirs; zdroje nemoci; Československo